2014
DOI: 10.1021/es503438e
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and Retention of 99-Tc(IV) in Magnetite under High pH Conditions

Abstract: Technetium incorporation into magnetite and its behavior during subsequent oxidation has been investigated at high pH to determine the technetium retention mechanism(s) on formation and oxidative perturbation of magnetite in systems relevant to radioactive waste disposal. Ferrihydrite was exposed to Tc(VII)(aq) containing cement leachates (pH 10.5-13.1), and crystallization of magnetite was induced via addition of Fe(II)aq. A combination of X-ray diffraction (XRD), chemical extraction, and X-ray absorption spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 77 publications
7
114
1
Order By: Relevance
“…The Fe(II)-induced crystallization of ferrihydrite to magnetite was studied in U(VI)-amended synthetic cement leachates chosen to simulate early-(pH 13.1) and late-( pH 10.5) stage evolution of a GDF (Berner, 1992;Marshall et al, 2014a;Moyce et al, 2014 2-line ferrihydrite was synthesized (Cornell and Schwertmann, 2003) and the Fe(III) content was determined by dissolution in 1 M HCl and analysis (Viollier et al, 2000). Ferrihydrite was equilibrated with the cement leachates at 4 g l -1 for 1 hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The Fe(II)-induced crystallization of ferrihydrite to magnetite was studied in U(VI)-amended synthetic cement leachates chosen to simulate early-(pH 13.1) and late-( pH 10.5) stage evolution of a GDF (Berner, 1992;Marshall et al, 2014a;Moyce et al, 2014 2-line ferrihydrite was synthesized (Cornell and Schwertmann, 2003) and the Fe(III) content was determined by dissolution in 1 M HCl and analysis (Viollier et al, 2000). Ferrihydrite was equilibrated with the cement leachates at 4 g l -1 for 1 hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is suggested that alteration of the glasses under thoroughly reducing conditions sustained over very long time will keep the Tc ions confined to an insoluble secondary phase akin to pyrolusite, thus preventing their hazardous accumulation in the biosphere. Recent research suggests that Tc(IV) ions can be sorbed onto FeS 2 surfaces or incorporated in iron oxides such as hematite (α‐Fe 2 O 3 ) or magnetite (Fe 3 O 4 ) as well as iron oxihydroxides such as goethite (α‐FeOOH) . The mechanism relies on direct substitution of Tc(IV) onto Fe(III) lattice sites that may be retained stably under environmental conditions to be expected in a nuclear waste disposal vault.…”
Section: Extension To Nuclear Waste Glassesmentioning
confidence: 99%
“…Schematics of the sequence of major interaction, leaching and precipitation reactions determining the corrosion mechanisms of glass (redrawn after Wicks)…”
Section: Extension To Nuclear Waste Glassesmentioning
confidence: 99%
“…In all spinel, oxygen is arranged in a face-centered-cubic lattice, wherein these sites are situated. [36,37]. The short-lived 99m Tc isotope has also been added to magnetite particles for use in medical imaging [38].…”
Section: Spinelmentioning
confidence: 99%
“…Sintering oxides at pressures of GPa has been shown to create MgFe 2 O 4 spinel with up to 0.35 mass% rhenium, [54]. Rhenium is a non-radioactive chemical surrogate for Tc, with similar volatility and chemical speciation [6,36].This is meant to mimic the geological conditions that yield Re-bearing spinel, with concentrations on the order of fractions of ~1 ng Re/g of spinel [55].…”
Section: High-temperature Sinteringmentioning
confidence: 99%